Chromatinized Protein Kinase C-θ: Can It Escape the Clutches of NF-κB? - Sutcliffe, Elissa L.; Li, Jasmine; Zafar, Anjum; Hardy, Kristine; Ghildyal, Reena; McCuaig, Robert; Norris, Nicole; Lim, Chloe; Milburn, Peter J.; Casarotto, Marco; Denyer, Gareth; Rao, Sudha (Frontiers in Immunology, 2012)
We recently provided the first description of a nuclear mechanism used by PKC-theta to mediate T cell gene expression. In this mode, PKC-theta tethers to chromatin to form an active nuclear complex by interacting with proteins including RNA polymerase II, the histone kinase MSK-1, the demethylase LSD-1 and the adaptor molecule 14-3-3zeta at regulatory regions of inducible immune response genes. Moreover, our genome-wide analysis identified many novel PKC-theta target genes and microRNAs implicated in T cell development, differentiation, apoptosis and proliferation. We have expanded our ChIP-on-chip analysis and have now identified a transcription factor motif containing NF-kB that may facilitate recruitment of PKC-theta to chromatin at coding genes. Furthermore, NF-kB association with chromatin appears to be a prerequisite for the assembly of the PKC-theta active complex. In contrast, a distinct NF-kB containing module appears to operate at PKC-theta targeted microRNAs, and here NF-kB negatively regulates microRNA gene transcription. Our efforts are also focussing on distinguishing between the nuclear and cytoplasmic functions of PKCs to ascertain how these kinases may synergise their roles as both cytoplasmic signalling proteins and their functions on the chromatin template, together enabling rapid induction of eukaryotic genes. We have identified an alternative sequence within PKC-theta that appears to be important for nuclear translocation of this kinase. Understanding the molecular mechanisms used by signal transduction kinases to elicit specific and distinct transcriptional programs in T cells will enable scientists to refine current therapeutic strategies for autoimmune diseases and cancer.